3D and 4D seismic investigations of fluid flow and gas hydrate systems - Waage, Malin (Geochemistry, Geophysics, Geosystems, 2019)
Using the state-of-the-art high resolution P-Cable 3D seismic system, in this thesis we (1) study the shallow strata (<1km below seabed) and describe the geological controls and driving mechanisms for fluid leakage at two sites in the northern Barents Sea, and (2) introduce a new time-lapse seismic method for high-frequency (~30-350 Hz) P-Cable seismic data. The study areas are interesting as they are located close to the upper termination of the gas hydrate stability zone and may experience ongoing or past growth and decomposition of gas hydrates. Bjørnøyrenna area hosts over 100 km-wide craters – a possible result of methane blowouts in the past. In Storfjordrenna, methane venting associates to gas hydrate bearing mounds (pingos). The northern Barents Sea is an underexplored area compared to the southern Barents Sea open for petroleum exploration. Therefore, our studies provide unique insight into the architecture and nature of shallow methane accumulations, fluid flow dynamics and gas hydrate inventories connected to thermogenic gas reservoirs that are deemed to occur elsewhere in the region. Our results point towards different geological controls on fluid flow. In Storfjordrenna, methane from Paleocene strata migrates along permeable beds and extensional faults linked to the regional Hornsund Fault Complex, accumulates under Quaternary glacial tills and locally forms gas hydrate chimneys. The Bjørnøyrenna lacks a glacial cover and the craters are incised in lithified, yet fractured, Triassic bedrocks. The source and reservoir of methane here is shallow Triassic clinoforms widespread across the Barents Sea. Furthermore, using 6 P-Cable 3D seismic datasets from three areas with and without known active fluid flow, we test seismic repeatability at various geological setting and develop an optimal workflow for 4D seismic approach. The results show high potential of such high-resolutions time-lapse seismic studies to reveal natural fluid flow dynamics on a yearly time scale.